ОСОБЛИВОСТІ РИНКУ ОСВІТНІХ ПОСЛУГ І ПРОБЛЕМА ВЗАЄМОДІЇ ВНЗ З РОБОТОДАВЦЯМИ (International Journal of Innovative Technologies in Economy, 2020)
The purpose of the article is to analyze the current processes that are taking place in the field of training for the national economy of Ukraine, and to develop ways to improve the effectiveness of interaction and interconnection of labor markets and educational services. The problem of social partnerships between higher education institutions and the real economy is investigated. This paper analyzes the foreign experience of networking universities with employers, and highlights the successes and challenges of this process. The content of the mechanism of interaction between customers and consumers in the educational services market is considered. It also offers suggestions on how to make the education market more up-to-date and adapted to the development of everything new in the Ukrainian labor market. The necessity of regulating the interaction of educational services and labor markets is substantiated. It is proved that only the interaction of professional educational institutions, employers and the state can ensure the effective functioning of the market of educational services, which provides the balance of demand and supply of qualified personnel necessary for the successful economic development of the country.